Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/cas.13186
|View full text |Cite
|
Sign up to set email alerts
|

SOX2 is required to maintain cancer stem cells in ovarian cancer

Abstract: Ovarian cancer cells can form spheroids under serum‐free suspension culture conditions. The spheroids, which are enriched in cancer stem cells, can result in tumor dissemination and relapse. To identify new targetable molecules in ovarian cancer spheroids, we investigated the differential expression of genes in spheroids compared with that under monolayer culture conditions by qPCR microarray. We identified that SOX2 is overexpressed in spheroids. We then proved that SOX2 expression was increased in successive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 45 publications
10
54
0
Order By: Relevance
“…Expression of transcription factor SOX2 is one of the hallmarks of embryonic stem cells, induced pluripotent stem cells and CSCs. The relationship between the expression of SOX2 and CSCs population was identified in breast cancer[12], lung cancer[1517], ovarian cancer[18–20], and cervical cancer [21]. In our previous study, SOX2-positive cells isolated from the cervical cancer cell lines SiHa and C33A were found to exhibit self-renewal, differentiation, and tumor initiating properties, which are major characteristics of CSCs[7].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of transcription factor SOX2 is one of the hallmarks of embryonic stem cells, induced pluripotent stem cells and CSCs. The relationship between the expression of SOX2 and CSCs population was identified in breast cancer[12], lung cancer[1517], ovarian cancer[18–20], and cervical cancer [21]. In our previous study, SOX2-positive cells isolated from the cervical cancer cell lines SiHa and C33A were found to exhibit self-renewal, differentiation, and tumor initiating properties, which are major characteristics of CSCs[7].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, transduction of SOX2 into OC cell lines also enhanced resistance to cell apoptosis through overexpression of the anti-apoptotic gene BCL2 and simultaneous down-regulation of the pro-apoptotic genes PUMA/BBC3 and NOXA/PAMAIP1 34 . Overexpression of SOX2 also accelerated cell migration by down-regulating E-cadherin and up-regulating vimentin expression 31 . These results at the cellular level were not as the same as the results based on clinical samples, which suggested that in vitro studies could not imitate the environment in the body completely.…”
Section: Sox Genes In Gcsmentioning
confidence: 93%
“…Knockdown of SOX2 in cell lines accordingly decreased chemoresistance to cisplatin via down-regulating expression of ABCB1 , ABCG2 , and ABCC6 31 . These results were accordance with those of researches on the roles of SOX2 based on OC cell lines, but not with researches based on patients’ samples in other cases 9,31,34,38,39 . Further simultaneous in vitro and in vivo researches into SOX2 are therefore needed to develop its role as a promising new therapeutic target for patients with OC.…”
Section: Sox Genes In Gcsmentioning
confidence: 97%
See 2 more Smart Citations